Redesigning Rural Education Ideas for Action. - Mid-Continent Regional Educational Lab., Aurora, CO.; Mid-Continent Regional Educational Lab., Aurora, CO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
This brochure offers descriptions of three Mid-continent Regional Educational Laboratory (McREL) programs designed to improve elementary and secondary education in the midwestern United States. "Project ACCESS" helps students explore career options. "Decisions About Technology" helps increase learning opportunities through the use of computer technology. "Rural School and Community Development" helps students and community interact to improve the economic health of the community. Clustering schools is a way of dealing with declining money and resources. Sharing teachers, students and equipment can be positive alternatives to reductions in staff, student enrollment, and equipment. Linkages through computer or video networks among schools successfully reach local colleges, employers, and community organizations. Capsule descriptions of 28 working rural programs, including rural school organizations, community study projects, and technology programs, are provided; the name and address of a contact person is included for each program. A list of related McREL publications concludes the document. (TES)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: 400-86-0002.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Counseling; Community Development; Educational Improvement; Elementary Secondary Education; Local Area Networks; Program Descriptions; Rural Education; Black Hills State College SD -- Mid Continent Regional Educational Laboratory -- Missouri -- North Dakota -- South Dakota; Reports, Descriptive; Opinion Papers